Pelaksanaan Asas Hukum Retroaktif terhadap Penegakan Hukum Pidana dalam Rangka Efektivitas Pengembalian Keuangan Negara - Subarysah Subarysah (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2018)
The consequence of within the legality principle in Indonesian legislation is the prohibition of retroactively imposing a criminal legislation or known as non-retroactive, related to the financial losses of the state especially regarding the criminal act of corruption that occurred prior to the issuance of the law, retroactive law in the return of state finances based on the losses incurred to the state caused by a crime, in principle regulated in the PTPK Law because one of the purposes of the enactment of Law no. 31 of 1999 in conjunction with Law no. 20 of 2001 is to restore the state losses. Therefore, the enforcement of criminal law prioritizes the return of state money from corruptor actors, how is the implementation of retroactive legal principle in criminal law enforcement in the framework of effectiveness of state financial return as well as what implications and constraints that arise in the mechanism of implementation of retroactive legal principle in rangaka settlement of state finances.